2023
DOI: 10.1007/s12072-022-10469-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation of steatosis and non-alcoholic fatty liver disease in adolescence

Abstract: Background and aims Epigenetic modifications are associated with hepatic fat accumulation and non-alcoholic fatty liver disease (NAFLD). However, few epigenetic modifications directly implicated in such processes have been identified during adolescence, a critical developmental window where physiological changes could influence future disease trajectory. To investigate the association between DNA methylation and NAFLD in adolescence, we undertook discovery and validation of novel methylation mark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Since altered DNA methylation has been identified as a key determinant of MASLD pathogenesis ( Li et al, 2018 ; Hyun and Jung, 2020 ; Lai et al, 2020 ; Bu et al, 2022 ; Kuramoto et al, 2022 ; Melton et al, 2023 ), we next applied Infinium mouse methylation Beadchip array studies to map genome-wide DNA methylation changes in liver biopsies of WT and hepatocyte-specific PPARα KO mice, following 6-week chow or CDAHFD diet. As shown in Figure 4 , the WT mice on a CDAHFD show predominant hypermethylation of the promotor region of PPARα compared to the WT mice on a chow diet, which could explain the gradual silencing of PPARα expression following a 6-week CDAHFD diet.…”
Section: Resultsmentioning
confidence: 99%
“…Since altered DNA methylation has been identified as a key determinant of MASLD pathogenesis ( Li et al, 2018 ; Hyun and Jung, 2020 ; Lai et al, 2020 ; Bu et al, 2022 ; Kuramoto et al, 2022 ; Melton et al, 2023 ), we next applied Infinium mouse methylation Beadchip array studies to map genome-wide DNA methylation changes in liver biopsies of WT and hepatocyte-specific PPARα KO mice, following 6-week chow or CDAHFD diet. As shown in Figure 4 , the WT mice on a CDAHFD show predominant hypermethylation of the promotor region of PPARα compared to the WT mice on a chow diet, which could explain the gradual silencing of PPARα expression following a 6-week CDAHFD diet.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, it is a global medical issue, and more than 25% of the general population worldwide suffers from NAFLD [59]. Epigenetic modifications combined with NAFLD are related to type 2 diabetes mellitus and other metabolic diseases [60,61]. Physiological changes in adolescence in short intervals contribute to dysmetabolism, which may lead to early liver damage [62].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed DNA methylation changed in liver biopsy of patients with NAFLD 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] (Figure 3). A recent investigation revealed a marked reduction in global DNA methylation among 47 individuals diagnosed with NAFLD compared to a cohort of 18 lean subjects without NAFLD, as assessed via liver biopsy.…”
Section: Clinical Researchmentioning
confidence: 95%